Дослідження сонячних колекторів, інтегрованих у конструкцію скляного фасаду будівлі/споруди: необхідність та особливості - Венгрин, І.; Venhryn, Iryna (Видавництво Львівської політехніки, 2019)
Проаналізовано необхідність розроблення сонячних колекторів, інтегрованих у конструкцію будівлі/споруди скляного фасаду. Обґрунтовано необхідність розвитку в Україні відновлюваних джерел енергії за рахунок параметра енергоємності валового внутрішнього продукту України та фізичного зношення установок в паливно-енергетичному комплексі. Обґрунтовано, що сонячна енергетика як один з видів загальнодоступних ресурсів у сфері альтернативних технологій має перспективи розвитку. В праці знайдено нові технологічні рішення, що дають змогу поєднати сонячне електро- і теплопостачання з урахуванням тенденції еволюції скляних фасадів. Для дослідження описано методи випробувань сонячних колекторів і фотоелементів відповідно до нормативної літератури. Основні критерії, що впливають на коефіцієнт корисної дії в конструкції, такі: інтенсивність випромінювання сонячної енергії, температура навколишнього середовища, конструктивні особливості та встановлені експлуатаційні характеристики сонячного колектора.

The work is devoted to the analysis of the need for the development of solar collectors integrated into the design of the building / structure glass facade. In particular, the necessity for Ukraine to develop renewable energy sources through the parameter of energy intensity of the Ukraine gross domestic product and the physical wear of the installation in fuel-energy complex. It was analyzed that the solar energy as one of the types of generally available resources in the field of alternative technologies has been prospects for development. Through the using of very small amount of solar energy installations in comparison with the solar energy volume that receives the Earth's surface relative to energy consumption on Earth, it can be seen the prospects of such resource. It has been noted that the territory of Ukraine receives a sufficient amount of solar energy for its use by solar installations. In this paper, conducts the search of new alternative technological solutions that allow to combine the installation of solar eletro- and heat supply with the design of the glass facade in view of the trend of glass facades evolution in developed countries. Test methods of solar collectors and solar cells according to the normative literature are described for the research. The main criterias that determine the coefficient of performance parameter are: the intensity of solar energy radiation, the ambient temperature, the design features of the solar collector, the initially established operating the solar collector characteristics. The factors that should have a significant impact on the efficiency of the design are determined for the laboratory stand study. In particular: the distance between the solar cell and the solar collector; the simulated intensity flow of thermal energy; the angle between active surface of the solar collector and the projection of the heat flow direction in the vertical plane of the solar collector; heat carrier flow rate installed in the solar heating system; air velocity; the angle between active surface of the solar collector and the projection of the wind flow direction in the vertical plane of the solar collector; the angle between the solar collector surface and the projection of the heat flow direction in the horizontal plane of the solar collector.
Research of solar collectors integrated into the design of the building/structure glass facade: necessity and features
Keywords: сонячна енергія; сонячний колектор; фактор; скляний фасад; фотоелемент; solar energy; solar collector; factor; glass facade; solar cell